AIoT: a taxonomy, review and future directions - Jiyi WU; Wenjuan LI; Jian CAO; Shiyou QIAN; Qifei ZHANG; Rajkumar BUYYA (Dianxin kexue)
AIoT (artificial intelligence of things) is an integrated product of artificial intelligence (AI) and internet of things (IoT).Currently, it has been widely used in smart cities, smart homes, smart manufacturing, and driverless.However, the research of AIoT is still in its infancy, facing with many problems and challenges.In order to clarify the concept and provide possible solutions, a comprehensive survey was carried out on AIoT.Firstly, a clear definition of AIoT was provided, along with the brief introduction on its background and application scenarios.And then a novel cloud-edge-end hybrid AIoT architecture for intelligent information processing was constructed.Based on the research framework of AIoT, the research status and solutions were discussed, including AI integrated IoT data acquisition, complex event processing and coordination, cloud-edge-end integration, AI-enhanced IoT security and privacy, and AI-based applications, etc.Finally, it identified the open challenges and offers future research directions.